Diagnosis of Beckwith–Wiedemann syndrome in children presenting with Wilms tumor. Issue 10 (22nd June 2018) - MacFarland, Suzanne P.; Duffy, Kelly A.; Bhatti, Tricia R.; Bagatell, Rochelle; Balamuth, Naomi J.; Brodeur, Garrett M.; Ganguly, Arupa; Mattei, Peter A.; Surrey, Lea F.; Balis, Frank M.; Kalish, Jennifer M.
Abstract: Beckwith–Wiedemann syndrome (BWS) is a genetic syndrome associated with overgrowth and cancer predisposition, including predisposition to Wilms tumor (WT). Patients with BWS and BWS spectrum are screened from birth to age 7 years for BWS‐associated cancers. However, in some cases a BWS‐associated cancer may be the first recognized manifestation of the syndrome. We describe 12 patients diagnosed with BWS after presenting with a WT. We discuss the features of BWS in these patients and hypothesize that earlier detection of BWS by attention to its subtler manifestations could lead to earlier detection of children at risk for associated malignancies.